Influence of dietary tryptophan levels on the growth performance of segregated early-weaned pigs (10 to 20 lb) - J A Loughmiller; D A Knabe; K Hongtrakul; P R O'Quinn; S Moser; J W Smith II; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1997)
A total of 360 pigs (averaging 13 d of age and 9.4 lb) was used to determine the effects of increasing dietary tryptophan:lysine ratio on the growth performance of segregated early-weaned (SEW) pigs. Two apparent digestible lysine levels (1. 15 and 1.50 %) and six apparent digestible tryptophan: lysine ratios (12.5, 15, 17.5, 20, 22.5 and 25%) were fed from d 0 to 16 after weaning. Lysine x tryptophan interactions were observed for ADG and F/G. Increasing the tryptophan: lysine ratio in the low lysine diets improved ADG and F/G in a quadratic manner. Increasing the tryptophan level had no effect in the high lysine diets. Results of this trial indicate that optimal apparent digestible tryptophan: lysine ratio is approximately 15 %.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; SEW pig; Tryptophan; Lysine